Is the current surge in political and financial attention to One Health solidifying or splintering the movement? - Julia Spencer; Ellen McRobie; Osman Dar; Afifah Rahman-Shepherd; Nadeem Hasan; Johanna Hanefeld; Mishal Khan (BMJ Global Health)
Introduction The global health field has witnessed the rise, short-term persistence and fall of several movements. One Health, which addresses links between human, animal and environmental health, is currently experiencing a surge in political and financial attention, but there are well-documented barriers to collaboration between stakeholders from different sectors. We examined how stakeholder dynamics and approaches to operationalising One Health have evolved further to recent political and financial support for One Health.Methods We conducted a mixed methods study, first by qualitatively investigating views of 25 major policymakers and funders of One Health programmes about factors supporting or impeding systemic changes to strengthen the One Health movement. We then triangulated these findings with a quantitative analysis of the current operations of 100 global One Health Networks.Results We found that recent attention to One Health at high-level political fora has increased power struggles between dominant human and animal health stakeholders, in a context where investment in collaboration building skills is lacking. The injection of funding to support One Health initiatives has been accompanied by a rise in organisations conducting diverse activities under the One Health umbrella, with stakeholders shifting operationalisation in directions most aligned with their own interests, thereby splintering and weakening the movement. While international attention to antimicrobial resistance was identified as a unique opportunity to strengthen the One Health movement, there is a risk that this will further drive a siloed, disease-specific approach and that structural changes required for wider collaboration will be neglected.Conclusion Our analysis indicated several opportunities to capitalise on the current growth in One Health initiatives and funding. In particular, evidence from better monitoring and evaluation of ongoing activities could support the case for future funding and allow development of more precise guidelines on best practices.